PREVALENCE OF HELMINTH EGGS IN SOILS OF SELECTED PUBLIC AND PRIVATE PRIMARY SCHOOLS IN KALTUNGO, GOMBE STATE, NIGERIA - admin, MUSA, A. M; IBRAHIM, R; ABDULKADIR, H. U.,; UMAR, F. I; ABUBAKAR, B.,; MUHAMMAD, S. U.; ABDULLAHI, J. K (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Helminths are group of parasites causing neglected tropical diseases of public health concern. It is important to map out soil contaminated with helminth eggs in selected primary schools and to project which school need health. This study screen soil samples for the prevalence of helminth eggs in soils of selected public and private primary schools in Kaltungo. A total of 280 (two hundred and eighty) Soil samples were collected from the ten randomly selected schools and Chi-square test was used to test for associations. The overall prevalence was (73.93) of helminth eggs found in public and private primary schools. There was statistically significant different (p < 0.05) in prevalence of helminth eggs in soil samples of public and private schools. The highest species-specific prevalence was Ancylostomaduodenaleeggs with 285(26.71% prevalence) with a mean of 146.5 ± 69.25, while the least specie was Trichuristrichiuraeggs with 30(2.81% prevalence) There was a significant association between the occurrence of helminth egg and season (χ2 = .5.9031, p = 0.015). The result of the study therefore indicates that there is high prevalence rate of helminths eggs in the selected primary schools within Kaltungo Metropolis. Therefore, there is a need of regular deworming of the school children and sanitary majors of the school premises should all be improved.